2021
DOI: 10.1371/journal.pone.0257208
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel factor analysis of flipped classroom in dental education: A 3-year randomized controlled trial

Abstract: Purpose Previous studies have rarely attempted to test the confounding factors that may affect learning outcomes of the flipped classroom. The purpose of this study was to assess how flipped classrooms affect the acquisition of knowledge in clinical dental education based on multilevel factor analysis. Method The authors conducted a 3-year (2017, 2018, and 2019) randomized controlled trial in a series of introductory prosthodontics courses in dental education. A total of 137 participants were randomly assign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 32 publications
3
14
1
2
Order By: Relevance
“…The results showed that the ipped method was more effective. This result is in line with the research of Gallardo et al, Wang et al, and Ozcan, who compared the nal scores of dental students in the ipped classroom and face-to-face training (49)(50)(51).…”
Section: Discussionsupporting
confidence: 91%
“…The results showed that the ipped method was more effective. This result is in line with the research of Gallardo et al, Wang et al, and Ozcan, who compared the nal scores of dental students in the ipped classroom and face-to-face training (49)(50)(51).…”
Section: Discussionsupporting
confidence: 91%
“…Fourteen duplicated studies, one non‐RCT study and seven studies that had no association with flipped classroom were excluded after the title and abstracts were read. Finally, we identified 15 eligible articles (Beom et al, 2018; Dombrowski et al, 2018; Elledge et al, 2018; He et al, 2019; Kühl et al, 2017; Ling et al, 2016; Lu et al, 2021; Moll‐Khosrawi et al, 2021; Nakanishi et al, 2017; Riddell et al, 2017; Rose et al, 2016; Rui et al, 2017; Tang et al, 2017; Wang et al, 2021; Yang et al, 2020). Table 2 summarizes the characteristics of these papers.…”
Section: Resultsmentioning
confidence: 99%
“…There is more than one index for evaluating the effect of teaching in medical education, but many RCTs only focus on a single index, which makes it difficult to compare and evaluate their results. In addition, the teaching effect of flipped classroom still remains uncertain, and relatively few studies have assessed the factors affecting its effectiveness (Wang et al, 2021). Good quality RCTs are very important for studying the effectiveness of flipped classroom.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been frequently noted that relatedness between students as peers, as well as between students and their instructors is important to persistence and the achievement of desired learning outcomes ( Bower et al, 2015 ; Chickering & Gamson, 1991 ; Kuh et al, 2010 ; Raes et al, 2020 ). While some research has shown relatedness is hampered for students learning in the virtual realm ( Raes et al, 2020 ), others have noted the design and thoughtful deployment of virtual instruction can temper this shortcoming ( Strayer, 2012 ; Wang et al, 2021 ). For example, employing a blended rather than exclusively virtual approach has often proven an effective strategy as has the deployment of flipped classroom instructional elements.…”
Section: Literature Reviewmentioning
confidence: 99%